FAKTOR-FAKTOR YANG MEMPENGARUHI RISIKO KREDIT PADA SEKTOR PERBANKAN YANG TERDAFTAR DI BEI - Wiwi Handayani; Henny Setyo Lestari (Institut Shanti Bhuana, Program Studi Kewirausahaan, 2022)
This study aims to analyze the internal and external factors of banking on non-performing loans. This study uses independent variables, namely bank size, capital adequacy ratio, bank performance, loan growth, bank inefficiency, ownership concentration, diversification, GDP growth, inflation and unemployment with the dependent variable being non-performing loans. The sample used was 35 banks listed on the Indonesia Stock Exchange for the 2016-2020 period. The analytical method used is multiple regression panel data analysis. The results show that bank size, bank capitalization, bank performance, ownership concentration, gross domestic product growth, inflation, and unemployment have a significant effect on Non Performing Loans. The results are expected to be a reference for managers and investors in looking at the factors that will affect the level of bank credit risk.